"A child may be tall but stunted." Meanings attached to childhood height in Tanzania. Issue 3 (6th February 2019) - Mchome, Zaina; Bailey, Ajay; Darak, Shrinivas; Haisma, Hinke
Abstract: Stunting affects large numbers of under‐fives in Tanzania. But do caretakers of under‐fives recognize height as a marker of child growth? What meanings do they attach to linear growth? An ethnographic study using cultural schemas theory was conducted in a rural community in Southeastern Tanzania to investigate caregivers' conceptualizations of child height in relation to growth and the meanings attached to short stature. Data for the study were collected through 19 focus group discussions, 30 in‐depth interviews, and five key informant interviews with caregivers of under‐fives, including mothers, fathers, elderly women, and community health workers. Principles of grounded theory guided the data management and analysis. Although caregivers could recognize height increments in children and were pleased to see improvements, many held that height is not related to nutrition, health, or overall growth. They referred to short stature as a normal condition that caregivers cannot influence; that is, as a function of God's will and/or heredity. While acknowledging short stature as an indicator of stunting, most participants said it is not reliable. Other signs of childhood stunting cited by caregivers include a mature‐looking face, wrinkled skin, weak or copper‐coloured hair, abnormal shortness and thinness, delayed ability to crawl/stand/walk, stunted IQ, and frequent illness. Culturally, a child could be tall but also stunted. Traditional rather than biomedical care was used to remedy growth problems in children. Public health programmers should seek to understand the local knowledge and schemas of child stature employed by people in their own context before designing and implementing interventions.